2000
DOI: 10.1007/10722515_16
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs in a Secure Jini Service Architecture

Abstract: Abstract.Jini is an infrastructure built on top of the mobile code facilities of the Java programming language enabling clients and services to spontaneously engage in arbitrary usage scenarios. For a small home or office environment the currently available infrastructure might be adequate, but for mission-critical applications it lacks essential security properties. In the sequel we identify weak points in the Jini architecture and its protocols and propose an extension to the architecture that provides a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Some typical research works on the improvement of Jini system security are as shown in [18][19][20]. The following shows some security requirements for Jini system commonly suggested by these works:…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Some typical research works on the improvement of Jini system security are as shown in [18][19][20]. The following shows some security requirements for Jini system commonly suggested by these works:…”
Section: Related Workmentioning
confidence: 99%
“…Reference [18] suggests a Jini service architecture to solve the establishment of trust between Lookup servers, service proxies, and servers and the requirements for access control, by implementing service in charge of authentication and permission-granting in the center of Jini federation. Reference [19] suggests a Jini security architecture and a method that establishes an authentication and authorization chain that connects server, service proxy, and user by using the certificate of SPKI (Simple Public Key Infrastructure).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nothing should be able to alter the state of the proxy object, either by intention or by fault. That means that the integrity of the proxy object must be ensured (Hasselmeyer et. al, 2000a).…”
Section: Proxy Object Issuesmentioning
confidence: 99%
“…Therefore the integrity and confidentiality of the communication has to be preserved, since the communication link might be intercepted, altered, or simulated by someone with malicious intentions. The privacy and anonymity of the client may be abused, because the client can not be ensured that the proxy does indeed provide the functionality it claims (Hasselmeyer et. al, 2000a).…”
Section: Proxy Object Issuesmentioning
confidence: 99%